Nanocrystalline Titanium Metal-Organic Frameworks for Highly Efficient and Flexible Perovskite Solar Cells - Ryu, UnJin; Jee, Seohyeon; Park, Joon-Suh; Han, Il Ki; Lee, Ju Ho; Park, Minwoo; Choi, Kyung Min (AMER CHEMICAL SOC, 2018)
Flexible perovskite solar cells (PSCs) have attracted considerable attention due to their excellent performance, low-cost, and great potential as an energy supplier for soft electronic devices. In particular, the design of charge transporting layers (CTLs) is crucial to the development of highly efficient and flexible PSCs. Herein, nano crystalline Ti-based metal-organic framework (nTi-MOF) particles are synthesized to have ca. 6 nm in diameter. These are then well-dispersed in alcohol solvents in order to generate electron transporting layers (ETLs) in PSCs under ambient temperatures using a spin-coating process. The electronic structure of nTi-MOF ETL is found to be suitable for charge injection and transfer from the perovskite to the electrodes. The combination of a [6,6]-phenyl-C-61-butyric acid (PCBM) into the nTi-MOF ETL provides for efficient electron transfer and also suppresses direct contact between the perovskite and the electrode. This results in impressive power conversion efficiencies (PCEs) of 18.94% and 17.43% for rigid and flexible devices, respectively. Moreover, outstanding mechanical stability is retained after 700 bending cycles at a bending radius (r) of 10 mm.
Keywords: HIGH-PERFORMANCE; LOW-TEMPERATURE; STABILITY; LAYER; TIO2; FILM